Column Study for the Removal of Colour from Batik Printing Effluent using Wastewater Sludge Carbon - Binti Amran , Nur Afiqah (Universiti Teknologi PETRONAS, 2018)
In wastewater treatment plant, sludge is one of the final products, channelled to dry bed which will be disposed regularly to waste disposal site. In another hand, batik printing industries in Malaysia does not have specified law addressed on colour treatment of dyed effluent before disposed to water bodies, which causes water pollution. This study utilizes the use of wastewater sludge carbon (WSC) as adsorbent, derived from sludge of a wastewater treatment plant to remove the colour of dyed effluent from batik printing industries. The sludge was collected from dry bed, the moisture was removed and then the sludge was burned in muffle furnace with temperature of 700° C for an hour to produce WSC. WSC produced was grounded and sieved to obtain Powdered WSC with sizes of 150 µm and 212 µm. The project continues by preparing three columns, with three different bed depths of 5 cm, 8 cm and 12 cm. Two set of column studies was conducted with different flow rate of 70 ml per hour, 36 ml per hour and16ml per hour. Peristaltic pump and in flow was monitored regularly to avoid discontinuity of the flow into the columns. The treated batik effluent was collected hourly and the colour (PtCo) of the treated effluent was measured using spectrophotometer. The effect of different bed depth and different flow rate against time on the removal of colour was observed and analysed. Thomas and Adams-Bohart model was applied to experimental data to predict the column performance theoretically. Wastewater Carbon Sludge (WSC) was found to be functioning as adsorbent well. Removal of colour shows that WSC able to remove the colour from batik wastewater up to 100 % removal and its efficiency increased as the residence time of wastewater onto WSC increased. Results obtained could be appreciated for removing colour of dyed effluent from batik industry using activated carbon derived from sludge of wastewater treatment plant.